PERBAIKAN KUALITAS PETIS KEPALA UDANG WINDU (Penaeus monodon) DENGAN PENAMBAHAN TEPUNG ARANG KAYU GALAM (Melaleuca cajuputi powell), SEKAM PADI (Oryza sativa L ) DAN TEMPURUNG KELAPA (Cocos nucifera) - Juhana Suhanda; Purnomo Purnomo (Fish Scientiae, 2019)
This research was conducted with time for 4 months which include the conduct of research, data analysis, report preparation. This study aims to make a paste shrimp head juice Windu quality with the addition of flour Galam wood charcoal, ricehusk and coconut shell. While its use is to produce a paste shrimp head juice Windu acceptable and preferred by consumers. This study used an experimental method based on the pattern and made completely randomized design ( CRD ) with four treatments, namely A ( without the addition of charcoal powder ), treatment B (addition of charcoal powder Galam 0.05 %), treatment C ( addition of rice husk flour 0 , 05 % ) and treatment D ( addition of coconut shell charcoal powder 0.05 % ). Each treatment was done 3 times repetition. The parameters tested include Protein LevelsTest, Test Water Content, Content Test Abu, Organoleptic Test is taste, color, aromaand texture. Acceptance or rejection of the hypothesis based on the results of the F test( analysis of variance ) From the results of the testing and analysis of the four treatments for the highest levels of the protein test is treatment D ( 26.60 % ), thelowest moisture content test is in treatment D ( 19 , 28 % ) and lowest ash content testis treatment A (7.77 % ), but among the treatments on ash content was notsignificantly different so that could mean ash content in each treatment did not differ( not significant ), whereas organoleptic test for taste , color , flavor and texturewhich is the highest treatment D is a sense of taste ( 6.89 ), color (7.31 ), flavor(6.48 ) and texture (6.635).